Technical note: using a high finesse optical resonator to provide a long light path for differential optical absorption spectroscopy: CE-DOAS - Meinen, Jan; Thieser, Jim; Platt, Ulrich; Leisner, Thomas (Atmospheric chemistry and physics, 2010)
Cavity enhanced methods in absorption spectroscopy have seen a considerable increase in popularity during the past decade. Especially Cavity Enhanced Absorption Spectroscopy (CEAS) established itself in atmospheric trace gas detection by providing tens of kilometers of effective light path length using a cavity as short as 1 m. In this paper we report on the construction and testing of a compact and power efficient light emitting diode based broadband Cavity Enhanced Differential Optical Absorption Spectrometer (CE-DOAS) for in situ observation of atmospheric NO3. This device combines the small size of the cavity with the advantages of the DOAS approach in terms of sensitivity, specificity and insensivity to intensity fluctuations of the light source. In particular, no selective removal of the analyte (here NO3) is necessary for calibration of the instrument if appropriate corrections are applied to the CEAS theory. Therefore the CE-DOAS technique can - in principle - measure any gas detectable by DOAS. We will discuss the advantages of using a light emitting diode (LED) as light source particularly the precautions which have to be considered for the use of LEDs with a broad wavelength range. The instrument was tested in the lab by detecting NO3 formed by mixing of NO2 and O3 in air. It was then compared to other trace gas detection techniques in an intercomparison campaign in the atmosphere simulation chamber SAPHIR at Forschungszentrum Jülich at NO3 concentrations as low as 6.3 ppt.